2017
DOI: 10.5005/jp-journals-10053-0051
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics in Laparoscopy

Abstract: Ergonomics is the science of best suiting the worker to his job, or to make the setting and surroundings favorable for the laparoscopic surgeon. The term was formally defi ned in 1949 and has brought benefi t and safety to many areas of human endeavor.1 The importance of ergonomics in the setting of laparoscopy cannot be overemphasized. Studies have shown that correct ergonomics can reduce suturing time.2 Pressurerelated chronic pain has been shown to be relieved by the use of ergonomically designed products.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…With regard to ergonomics, 41% said that laparoscopic surgery has poor ergonomics compared with open surgery, and there were some additional responses that it depended on the operating room setup. Yeola et al have shown that the layout of the operating room is important for surgeon comfort and have provided recommendations and guidelines to achieve ideal positioning. Improving ergonomics is frequently cited in the human literature as a key to reducing surgeon pain or discomfort .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to ergonomics, 41% said that laparoscopic surgery has poor ergonomics compared with open surgery, and there were some additional responses that it depended on the operating room setup. Yeola et al have shown that the layout of the operating room is important for surgeon comfort and have provided recommendations and guidelines to achieve ideal positioning. Improving ergonomics is frequently cited in the human literature as a key to reducing surgeon pain or discomfort .…”
Section: Discussionmentioning
confidence: 99%
“…Yeola et al have shown that the layout of the operating room is important for surgeon comfort and have provided recommendations and guidelines to achieve ideal positioning. Improving ergonomics is frequently cited in the human literature as a key to reducing surgeon pain or discomfort . When participants were asked whether laparoscopic surgery had poor ergonomics compared with open surgery, 41% of respondents answered “yes,” and 43% answered “no,” with some others responding that it was case dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment was done as per the proforma. This was prepared on the basis of current ergonomic guidelines [3,8,10,11]. Demographic details of the surgeons were recorded along with the monthly frequency of MIS procedures they performed and years of experience of the surgeon.…”
Section: Methodsmentioning
confidence: 99%
“…The role of ergonomics is to analyse problems brought forth in the operating room and subsequently frame guidelines for creating a work environment that promotes safety and comfort for its operators, at the same time ensuring effectiveness and efficiency of the procedure being performed [2]. The term "Ergonomics" was formally defined in 1949 [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Poor posture is the main cause of pain during laparoscopic surgery [5]. Appropriate monitor height and position, table height, port placement, and design of handheld instruments can improve poor posture [6][7][8]. Correct ergonomics decreases musculoskeletal disorders, suturing time, and complications [9,10].…”
Section: Introductionmentioning
confidence: 99%